LIPUS inhibited the expression of inflammatory factors and promoted the osteogenic differentiation capacity of hPDLCs by inhibiting the NF‐κB signaling pathway. (21st September 2019) - Liu, Shan; Zhou, Mengjiao; Li, Jie; Hu, Bo; Jiang, Dan; Huang, Hong; Song, Jinlin
Abstract: Background and Objectives: As a chronic infectious disease, periodontitis could lead to tooth and bone loss. Low‐intensity pulsed ultrasound (LIPUS) is a safe, noninvasive treatment method to effectively inhibit inflammation and promote bone differentiation. However, the application of LIPUS in curing periodontitis is still rare. Our study aimed to explore the ability of LIPUS to inhibit inflammatory factors and promote the osteogenic differentiation capacity of human periodontal ligament cells (hPDLCs), and its underlying mechanism. Material and Methods: Human periodontal ligament cells were obtained and cultured from the premolar tissue samples for experiments. First, hPDLCs were treated for 24 hours using lipopolysaccharide (LPS) and then exposed to LIPUS (10 mW/cm 2, 30 mW/cm 2, 60 mW/cm 2, and 90 mW/cm 2 ) to determine the appropriate intensity to inhibit expression of the inflammatory factors interleukin‐6 (IL‐6) and interleukin‐8 (IL‐8) expression. The expression of IL‐6 and IL‐8 was detected by real‐time PCR and enzyme‐linked immunosorbent assay. The safety of the most appropriate intensity of LIPUS was tested by a cell counting kit 8 test and an apoptosis assay. Then, LPS‐induced hPDLCs were treated in osteogenic medium for 7‐21 days with or without LIPUS (90 mW/cm 2, 30 min/d) stimulation. The osteogenic genes RUNX2, OPN, OSX, and OCN were measured by real‐time PCR. Additionally, osteogenic differentiation capacity was determined using alkaline phosphatase (ALP) staining, ALP activity analysis, and Alizarin red staining. The activity of the nuclear factor‐kappa B (NF‐κB) signaling pathway was determined by western blotting, real‐time PCR, immunofluorescence, and pathway blockade assays. Results: Lipopolysaccharide significantly upregulated the production and gene expression of IL‐6 and IL‐8, while LIPUS stimulation significantly inhibited IL‐6 and IL‐8 expression in an intensity‐dependent manner. LIPUS (90 mW/cm 2 ) was chosen as the most appropriate intensity, and there was no detrimental influence on cell proliferation and status with or without osteogenic medium. In addition, consecutive stimulation with LIPUS (90 mW/cm 2 ) for 30 min/d for 7 days could also inhibit IL‐6 and IL‐8 gene expression, upregulate the expression of the osteogenesis‐related genes RUNX2, OPN, OSX, and OCN, and promote osteogenic differentiation capacity in osteogenic medium in inflamed hPDLCs. The NF‐κB signaling pathway was inhibited with LIPUS (90 mW/cm 2 ) via inhibition of the phosphorylation of IκBα and the translocation of p65 into the nucleus in inflamed hPDLCs. Additional investigations of the NF‐κB inhibitor, BAY 11‐7082, revealed that LIPUS (90 mW/cm 2 ) acted similarly to BAY 11‐7802 to inhibit the NF‐κB signaling pathway and increase osteogenesis‐related genes and promote the osteogenic differentiation capacity of inflamed hPDLCs. Conclusion: Low‐intensity pulsed ultrasound (90 mW/cm 2 ) stimulation could be a safe method to inhibit IL‐6 and IL‐8 in hPDLCs by inhibiting the NF‐κB signaling pathway. The effect of LIPUS (90 mW/cm 2 ) and BAY 11‐7082 on LPS‐induced inflammation demonstrated that both of these agents were capable of promoting osteogenesis‐related gene expression and osteogenic differentiation in hPDLCs, suggesting that the effect of LIPUS on the promotion of osteogenic activity could be mediated in part through its ability to inhibit the NF‐κB signal pathway. Hence, LIPUS could be a potential therapeutic method to cure periodontitis.